Associations between changes in the gut microbiota and liver cirrhosis: a systematic review and meta-analysis - Ye Liu; Ziwei Chen; Chang Li; Tianhan Sun; Xuanmei Luo; Boyue Jiang; Meilan Liu; Qing Wang; Tong Li; Jianfu Cao; Yayu Li; Yuan Chen; et al. (BMC Gastroenterology, 2025)
Abstract Objective Summaries of the relationships between the microbiota and liver cirrhosis and their conclusions are not consistent. This study describes microbial differences in patients with liver cirrhosis by performing a meta-analysis. Methods We searched PubMed, Embase, Web of Science, and the Cochrane Library and collected related articles published before March 10, 2024. Ratio of autochthonous to non-autochthonous taxa was calculated as the cirrhosis dysbiosis ratio (CDR). Using a random-effects model, the standard mean deviation (SMD) and 95% confidence interval (CI) were calculated. We subsequently performed subgroup, sensitivity, and publication bias analyses. cirrhosis dysbiosis ratio. Results A total of 53 eligible papers including 5076 participants were included. The pooled estimates revealed a moderately significant reduction in gut microbiome richness in patients with liver cirrhosis compared with controls, including the Shannon, Chao1, observed species, ACE, and PD indices, but no significant difference was observed for the Simpson index. Over 80% of the studies reported significant differences in β diversity. Families Enterobacteriaceae and Pasteurellaceae, belonging to the phylum Proteobacteria, along with the family Streptococcaceae and the genera Haemophilus, Streptococcus, and Veillonella, were significantly associated with liver cirrhosis compared to the control group. In contrast, the healthy group exhibited a higher abundance of the class Clostridia, particularly the families Lachnospiraceae and Ruminococcaceae, which are known for their diversity and role as common gut commensals. Furthermore, the class Bacilli, predominantly represented by the genus Streptococcus, was markedly enriched in the cirrhosis group. Conclusions The microbiota richness of liver cirrhosis patients was lower than that of healthy controls. Alterations in gut microbiota linked to liver cirrhosis were characterized by a decrease in Lachnospiraceae, Ruminococcaceae, and Clostridia and an enrichment of Enterobacteriaceae, Pasteurellaceae, Streptococcaceae, Bacilli, and Streptococcus.